1994
DOI: 10.1071/ea9940259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bunch trimming and leaf removal at flowering on maturity bronzing, yield, and other aspects of fruit quality of bananas in North Queensland

Abstract: This study examined the effects of bunch trimming and leaf removal on rate of bunch filling, severity of the maturity bronzing fruit peel disorder, and other yield and quality paramaters. There were 4 levels of leaf removal (4, 7, 10, 13 leaves retained) and 4 levels of bunch trimming (male bud retained, male bud removed, male bud and 2 hands removed, male bud and 4 hands removed) imposed on banana bunches at flowering. The experiment was carried out at South Johnstone, North Queensland. The 320 plants in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…We confirm here that So-Si ratio changes have a significant effect on fruit morphology, as previously demonstrated in several studies (Daniells et al, 1987(Daniells et al, , 1994Israeli et al, 1995;Johns 1996;Kurien et al, 2000;Jullien et al, 2001b;Mouen Bedimo et al, 2003;Chillet et al, 2006). We reveal, furthermore, a new effect of a So-Si ratio change on the fruit quality potential: when the sink is decreased by removal of many hands, the fruit susceptibility to crown rot decreases.…”
Section: Discussionsupporting
confidence: 77%
“…We confirm here that So-Si ratio changes have a significant effect on fruit morphology, as previously demonstrated in several studies (Daniells et al, 1987(Daniells et al, , 1994Israeli et al, 1995;Johns 1996;Kurien et al, 2000;Jullien et al, 2001b;Mouen Bedimo et al, 2003;Chillet et al, 2006). We reveal, furthermore, a new effect of a So-Si ratio change on the fruit quality potential: when the sink is decreased by removal of many hands, the fruit susceptibility to crown rot decreases.…”
Section: Discussionsupporting
confidence: 77%
“…However, the growth rate of banana fruit also seems to vary with the source/sink ratio during fruit growth. Removal of hands (thereby decreasing the sink size: Meyer, 1975;Daniells et al, 1994;Johns, 1996), leaf shading (reducing resource availability: Israeli et al, 1995) or bunch bagging (increasing sink demand by elevating the air temperature: Turner and Rippon, 1973;Ganry, 1975;Johns and Scott, 1989a, b;Daniells et al, 1992;Jannoyer and Chillet, 1998;Turner, 1998) modify fruit growth rates and, consequently, the commercial harvest date.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the accumulation of mass of the bunch with increasing number of leaves occurred concomitantly with the increase of the mass of the fruit of 4 th hand, which was the result of increased fruit size. In tropical conditions, the defoliation of banana 'Nanica' did not affect bunch mass and fruit size (VARGAS et al, 2009;GONZÁLEZ et al, 2012); however, in subtropical, there was a reduction in plants with less than 10 leaves (DANIELLS et al, 1994). Regardless of period, the bunch filling time increased with the number of leaves, but with a variation of only 15 days between plants with higher and lower number of leaves ( Figure 1F).…”
Section: Crop Protectionmentioning
confidence: 95%
“…This indicated that the increased availability of assimilates due to the higher number of leaves promoted the highest growth in fruit size ( Figure 1E) and extended the bunch filling period ( Figure 1F) as a consequence of physiological maturity, resulting in longer time to complete ripening ( Figure 1G). DANIELLS et al (1994) and RAMIREZ et al (2008) reported no effect of defoliation on postharvest period, while GONZÁLEZ et al (2012) reported no effect on physical-chemical characteristic of the fruit.…”
Section: Crop Protectionmentioning
confidence: 98%